NaCl Accumulation in Leaves of Two Salt-Secreting Mangrove Species in Sarudu Village, Pasangkayu Regency, Indonesia - Ilma Sahira; Isnainar Isnainar; Vita Indri Febriani; Musdalifah Nurdin; Amalia Buntu; Astija Astija (Biology, Medicine, & Natural Product Chemistry, 2026)
Mangroves are coastal vegetation with a high capacity to adapt to their environment, characterized by distinctive and unique root systems. This study aimed to determine the accumulation of salt (NaCl) in the leaves of two salt-secreting mangrove species in Sarudu Village, Pasangkayu Regency. The research employed a quantitative descriptive approach, with samples collected through a survey. Salt accumulation data were obtained through argentometric titration using the Mohr method. Environmental measurements in the mangrove forest of Sarudu Village showed an average air temperature of 30°C, salinity ranging from 29 to 30 ppt, and pH values between 7.0 and 7.1. The results indicated that the highest average salt accumulation in the leaves of Aegiceras corniculatum was recorded at Station 3 (6.08%), while the lowest was found at Station 1 (3.07%). Similarly, in Avicennia lanata, the highest NaCl accumulation was observed at Station 3 (5.33%), whereas the lowest occurred at Station 1 (2.92%). Station 3 exhibited the highest percentage of salt accumulation among all sampling stations, likely because it was located in a coastal area that was frequently inundated by seawater to a depth of approximately 20 cm.